Effective Management of School Personnel in Modern Conditions - Muzaffar Ummatovich Kurbanov (Researchparks Publishing, 2022)
Over the past years, the place of personnel management in the management system has changed many times. Along with this, the views, approaches and theoretical bases of scientists and practitioners who worked in this area were revised. The improvement of production, information and management technologies, as well as the reassessment of universal human values, made it possible to come closest to solving the central problem of mankind: overcoming the contradiction between a person and an organization, since the strength of an organization is, first of all, in human capital. This problem is studied in the works of many authors. In the works of these researchers, an attempt is made to integrate the developed knowledge in the field of personnel management, a set of rules, principles and technologies that can be used by managers in effective personnel management.